2014
DOI: 10.14814/phy2.12255
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic identification of connective tissue growth factor as an osteogenic protein within skeletal muscle

Abstract: Aging is associated with increasing incidence of osteoporosis; a skeletal disorder characterized by compromised bone strength that may predispose patients to an increased risk of fracture. It is imperative to identify novel ways in which to attenuate such declines in the functional properties of bone. The purpose of this study was to identify, through in silico, in vitro, and in vivo approaches, a protein secreted from skeletal muscle that is putatively involved in bone formation. We performed a functional ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The duplication was confirmed and precisely defined by a sub‐cloning experiment (Figure d). The mutation was further analyzed with three on‐line tools (PSIPRED, TMHMM2.0 and TMpred) to predict the structure of the mutant PiT‐2 (Buchan, Minneci, Nugent, Bryson, & Jones, ; Forrester et al, ; Kosciolek & Jones, ). According to TMHMM2.0 and TMpred, which predict the number of transmembrane domains, the duplication caused elongation of the last (XII) transmembrane domain.…”
Section: Resultsmentioning
confidence: 99%
“…The duplication was confirmed and precisely defined by a sub‐cloning experiment (Figure d). The mutation was further analyzed with three on‐line tools (PSIPRED, TMHMM2.0 and TMpred) to predict the structure of the mutant PiT‐2 (Buchan, Minneci, Nugent, Bryson, & Jones, ; Forrester et al, ; Kosciolek & Jones, ). According to TMHMM2.0 and TMpred, which predict the number of transmembrane domains, the duplication caused elongation of the last (XII) transmembrane domain.…”
Section: Resultsmentioning
confidence: 99%
“…CTGF is a mito-attractant that is involved in cell adhesion and fibrosis in many cell types, including myofibroblasts ( Ramazani et al, 2018 ). CTGF expression rises after muscle contraction and exercise ( Kivela et al, 2007 ; McLean et al, 2015 ) and is part of what appears to be a coordinated transcriptional response in muscle that involves a variety of extracellular matrix and associated genes that is activated by maneuvers that alter insulin sensitivity ( Richardson et al, 2005 ; Bajaj et al, 2007 ; Forrester et al, 2014 ). The lack of change in CTGF expression following exercise in insulin resistant muscle could be a marker of exercise-induced changes that raise insulin sensitivity or could be part of the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we did not evaluate pathological changes in periarticular bone and cartilage. However, suppression of HIF‐1 may have an effect on osteochondral remodeling because VEGF was reported to be an essential molecule in cartilage metabolism and bone formation and also because CTGF was suggested to be related to bone formation and remodeling processes. Although our histological studies showed no obvious pathological changes in periarticular bone and cartilage in the knee joint at least until 2 weeks after knee fixation, detailed and long‐term evaluation of bone/cartilage metabolism is needed in the future.…”
Section: Discussionmentioning
confidence: 99%